(untitled) (Physical Education, Health and Social Sciences, 2025)
The socio-political and religious trajectory of the Zikri community in Makran under the patronage and governance of the Buledi rulers, spanning from 1628 through the 18th century is defined as the “Golden Age” for the Zikri faith, as the Buledi chiefs—most notably figures like Sheh Qasim—not only embraced the faith but integrated its tenets into the administrative and cultural fabric of the region. The study examines how the Zikris established Koh-e-Murad as a central site of pilgrimage, effectively creating a distinct religious geography that challenged the orthodoxies of the period. Under Buledi protection, the community transitioned from a peripheral sect to a dominant regional power, fostering a unique Baloch identity that merged spiritual devotion with tribal governance. However, this period of prosperity was not without friction. The abstract analyzes the intensifying external pressures from the Khanate of Kalat and the broader Sunni world, which viewed the Zikri-Buledi alliance with growing suspicion. By investigating the 18th-century shift toward the Brahui-led military campaigns, the research highlights how the decline of the Buledis ultimately led to the systematic marginalization of the Zikris. Through a synthesis of oral traditions and colonial records, this paper argues that the Buledi era was foundational in shaping the modern Zikri consciousness, illustrating a rare historical moment where religious heterodoxy and political sovereignty achieved a fragile but profound synergy in the rugged landscape of Makran.